Inferior residual oil hydrodemetallization catalyst and preparation method thereof

The preparation of alumina support and active metal solutions with bimodal pore structures through technical means such as phenolic resins and organic acids, which solves the problems of poor pore structure and environmental pollution of residual oil hydrogenation catalysts, and achieves high-performance residual oil hydrogenation and demetalization Catalysts improve the stability and processing adaptability of the catalyst.

CN119236912AActive Publication Date: 2025-01-03PETROCHINA CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410885591.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-03
Publication Date
2025-01-03
Estimated Expiration
2044-07-03

AI Technical Summary

Technical Problem

The pore structure of existing residual oil hydrodemetalization catalysts is poor, the preparation process is very polluted, the environment is unfriendly, and the poor dispersion of active metals leads to insufficient stability, making it impossible to effectively treat inferior residual oil with high metal content.

Method used

The phenolic resin is used as a pore reamer to prepare a large pore alumina carrier with a bimodal pore structure under the action of low-carbon alcohol, and prepare a metal impregnation liquid through organic acid and hydrogen peroxide, and use a composite complexing agent to carry out active metal loading to reduce ammonia contamination. Improve the dispersion and stability of active metals.

Benefits of technology

The high-performance hydrogenation reaction performance of the catalyst is achieved, with excellent bimodal pore structure, environmentally friendly preparation process and high dispersion active metals, which extends the operation cycle of the catalyst and improves the processing adaptability of inferior residual oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236912A_ABST
    Figure CN119236912A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an inferior residual oil hydrodemetallization catalyst, which comprises the following steps: mixing hydrated alumina, phenolic resin and an adhesive, adding an aqueous solution containing low-carbon alcohol, kneading, forming, drying and roasting to obtain an alumina carrier; dissolving a metal compound by using organic acid and hydrogen peroxide, and adding a composite complexing agent to prepare a metal impregnation liquid; wherein the active metal compound comprises metals of the VIII group and the VIB group; the specific surface area of the inferior residual oil hydrodemetallization catalyst is 80-180 m < 2 > / g, the pore volume is 0.5-1.1 cm < 3 > / g, and the proportion of the pore volume corresponding to pore channels with the pore diameter larger than 100 nm in the total pore volume is not less than 10%. According to the invention, phenolic resin is used as a pore-enlarging agent, and is partially dissolved under the action of low-carbon alcohol, and a macroporous diffusion channel with the size of more than 100nm is formed in the alumina carrier after extension crosslinking, so that the cost is low, thermoplasticity and thermoset are realized, the molding is easy, and the carrier strength is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst for hydrodemetallization of low-quality residual oil and a preparation method thereof, and in particular to a catalyst for hydrodemetallization of low-quality residual oil with a bimodal pore structure, good activity stability and high metal tolerance and a preparation method thereof, which is suitable for the hydroprocessing process of heavy low-quality residual oil with high metal content. Background Art

[0002] At present, the world's oil refining industry is facing the severe challenge of increasingly heavy and inferior crude oil resources. Residue oil usually accounts for 45-75% of crude oil, and its properties are significantly inferior to fractions such as gas oil with a lower boiling range. Therefore, the key to deep processing of crude oil to maximize the production of light products and chemical raw materials lies in the efficient conversion and utilization of residue oil.

[0003] Residue oil hydrogenation is the most effective processing technology for heavy and residual oil raw materials. Through hydrogenation, most of the impurities such as metals, sulfur and nitrogen in the residue oil are removed, and the residual carbon value is reduced, which is conducive to its further efficient processing and conversion. The technical combination of residue oil hydrogenation treatment and residue oil catalytic cracking (RFCC) has become a key technical path for processing inferior crude oil refining enterprises to improve economic benefits. The technical combination of residue oil hydrogenation treatment and residue oil catalytic cracking can not only maximize the conversion of residual oil with low utilization value and easy to cause environmental pollution, and greatly increase the yield of light oil; it can also obtain clean oil products with high added value and high quality. In a sense, the crude oil has been converted 100%, realizing the desire to squeeze out the crude oil in the process of oil refining. This technical combination has become the core technology for processing sulfur-containing crude oil refining enterprises to improve economic benefits.

[0004] Catalyst is the core of residue oil hydroprocessing technology, and plays a decisive role in the stable and efficient operation of residue oil hydroprocessing unit. The residue oil hydroprocessing process is different from the distillate oil hydroprocessing process. Its operating space velocity and operating cycle are much smaller than the latter. The catalyst loading is large and the deactivation is fast. Statistics show that about 40-50% of all types of hydrogenation catalysts are used in the residue oil hydroprocessing process.

[0005] Residue oil is the heaviest and poorest component in petroleum. It contains a large amount of colloids and asphaltene, has a large molecular weight, high density, high viscosity, strong polarity, high sulfur and carbon residue content, and is enriched with almost all metal impurities in petroleum. In the process of hydrogenation of residue oil, the metals such as Na, Ca, Ni, and V in the residue oil are deposited on the hydrogenation catalyst, which will cause permanent poisoning. This is a core factor to be considered in the hydrogenation process of heavy and poor residue oil. Hydrodemetallization (HDM) catalyst is one of the key technologies in the heavy oil hydrogenation process. Its main function is to remove most of the metal impurities such as Ni and V in the raw material, protect the downstream desulfurization (HDS) and denitrification (HDN) catalysts, and have a certain desulfurization capacity. This type of catalyst needs to have not only good metal removal ability, but also high metal impurity tolerance. Since most of the metal impurities in the residue oil exist in colloids and asphaltene, the diffusion resistance is large. The demetallization agent is restricted by the mass transfer and diffusion efficiency of the carrier, and is prone to pore blockage, and the deposition distribution of the removed impurities is seriously uneven, and the metal tolerance capacity is limited. All of the above result in a serious waste of the internal space of the catalyst, and the efficiency of the catalyst cannot be maximized. Therefore, such catalysts must have a large pore volume, pore diameter and good pore permeability to facilitate the diffusion, reaction and deposition of macromolecular substances such as asphaltene containing metal impurities in the residual oil raw material. One of the solutions is to use a bimodal pore structure carrier. During the reaction process, the macropores with a pore diameter of more than 100nm provide channels for the diffusion of macromolecular reaction substances, promoting the diffusion and deposition of impurities into the internal pores of the catalyst; while the pores with a pore diameter of less than 50nm provide reaction surfaces and deposition sites for impurities. The two types of pores work synergistically, so that the catalyst has high demetallization activity and high impurity tolerance.

[0006] On the other hand, in addition to having good hydrogenation and decontamination activity, the operation stability of the residue hydroprocessing catalyst is crucial. The activity stability of the residue hydroprocessing catalyst is closely related to its active phase structure, and the active metal needs to be highly dispersed on the carrier surface. Generally, the shorter the size of the active metal platelets and the fewer the number of layers, the better the dispersion and the better the catalyst activity stability. By developing a new active metal solution system that is simple to operate, environmentally friendly, and has excellent stability, the interaction between the carrier and the active metal is reduced, the dispersion of the active metal in the residue hydroprocessing catalyst is improved, the length and number of MoS2 platelets are reduced, and a larger proportion of 1-2 layers of MoS2 wafers are generated, thereby improving the activity and stability of the catalyst, improving the adaptability of inferior raw materials to processing during hydrogenation reactions, extending the operating cycle, and improving operating efficiency.

[0007] In the existing alumina carrier preparation technology, it is mostly necessary to add acidic substances such as nitric acid, acetic acid, aluminum nitrate, etc. as peptizing agents when forming alumina. The addition of acidic substances will destroy the particle structure of alumina and reduce the pore volume and pore size of the carrier. Using organic binders instead of peptizing acids for carrier forming can increase the pore volume and pore size of the carrier to a certain extent, but the effect is limited. The existing methods simply increase the macropore ratio of the carrier by adding pore expanders. When preparing bimodal pore structure carriers and catalysts with high macropore ratios, they face problems such as increased costs, difficult forming, and reduced strength.

[0008] In the preparation method of residual oil hydroprocessing catalyst, the traditional ammonia-containing alkaline metal impregnation liquid system uses a large amount of ammonia water, which causes environmental pollution problems. Ammonia gas overflows in large quantities during the production and preparation process, which has a strong odor and is environmentally unfriendly. In order to solve the ammonia pollution problem, the existing technology uses phosphoric acid and the like to prepare active metal impregnation liquids, but the active metals of the catalyst prepared by phosphoric acid have poor dispersibility, and the high phosphorus content leads to excessive acidity of the catalyst. The catalyst is easy to coke and deactivate quickly during the hydroprocessing process, and the stability is insufficient, which cannot meet the requirements of low-quality heavy residual oil hydroprocessing. Summary of the invention

[0009] The purpose of the present invention is to provide a residue oil hydrodemetallization catalyst and a preparation method having a bimodal pore structure, large pore volume and pore diameter, excellent stability, and a green and environmentally friendly preparation process, in order to solve the problems of poor pore structure, high pollution and environmental unfriendliness in the preparation process of existing residue oil hydrodemetallization catalysts, and insufficient stability due to poor active metal dispersibility, by developing a new carrier preparation and active metal loading method.

[0010] In view of the problems existing in the prior art, the present invention provides a method for preparing a catalyst for hydrodemetallization of low-quality residual oil, using phenolic resin as a pore-expanding agent to prepare a macroporous alumina carrier with a bimodal pore structure, solving the diffusion problem of low-quality residual oil macromolecular metal compounds and asphaltene, and effectively reducing the emission of pollutants such as ammonia in the production process by developing an environmentally friendly new active metal solution system and corresponding loading technology, making the catalyst production clean, and realizing high-dispersion loading of active metals to obtain a high-performance residual oil hydrodemetallization catalyst. The present invention provides a catalyst for hydrodemetallization of low-quality residual oil and a method for preparing the same, wherein the catalyst has an excellent bimodal pore structure, a large pore volume and pore diameter, an environmentally friendly and pollution-free production process, and the active metal presents a good state of high dispersion, low stacking, and short platelets on the catalyst. The catalyst is used in the residual oil hydroprocessing process and has excellent hydrogenation reaction performance.

[0011] The basic technical solution of the present invention to solve the problem is:

[0012] A method for preparing a catalyst for hydrodemetallization of low-quality residual oil comprises the following steps:

[0013] (1) Mixing hydrated alumina, phenolic resin and a binder, adding an aqueous solution containing a low-carbon alcohol, kneading, molding, drying and calcining to obtain an alumina carrier

[0014] (2) dissolving the metal compound by using organic acid and hydrogen peroxide, adding a complex complexing agent, and preparing a metal impregnation solution; impregnating the carrier in step (1), curing, drying and calcining to obtain a catalyst.

[0015] The preferred technical solution of the present invention is:

[0016] The hydrated aluminum oxide is selected from one or a mixture of gibbsite, boehmite, pseudo-boehmite and amorphous aluminum hydroxide, preferably pseudo-boehmite. They can be commercial products or prepared by any method in the prior art, such as pseudo-boehmite prepared by aluminum sulfate-sodium aluminate method;

[0017] The phenolic resin is a condensation product of phenol and formaldehyde, and can be thermosetting or thermoplastic or a mixture of the two, and its particle size is 80-3000 mesh, preferably 120-2000 mesh; the addition amount is 2-25wt%, preferably 5-20wt% based on alumina;

[0018] The binder is a synthetic cellulose selected from one or more of methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl methyl cellulose, preferably hydroxypropyl methyl cellulose, and the amount added is 1-5wt% based on alumina;

[0019] The viscosity of a 2% mass concentration aqueous solution of the synthetic cellulose at 20° C. is not less than 50,000 mPa·s;

[0020] The low-carbon alcohol is selected from one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol and glycerol, preferably methanol or ethanol, and the addition amount is 0.5-5wt% based on alumina;

[0021] The aqueous solution containing low-carbon alcohol has a temperature of 30-100° C., preferably 40-80° C.;

[0022] The alumina carrier has a drying temperature of 100-180°C, preferably 120-160°C; the carrier is calcined at a temperature of 500-1200°C, preferably 700-1000°C; and the calcination time is 1-4 hours;

[0023] The shape of the alumina carrier can be changed as needed, including but not limited to strip, sphere, Raschig ring, toothed ball, honeycomb, impeller, etc., wherein the strip shape includes but is not limited to cylinder, clover, four-leaf clover, butterfly, etc.;

[0024] The alumina carrier may be added with various additives as required, including but not limited to one or more of silicon, phosphorus, boron, titanium, zirconium, chlorine, fluorine and other elements. The alumina carrier may be added with various molecular sieves as required, including but not limited to one or more of X, Y, ZSM-5, β, phosphorus aluminum, titanium silicon, ZSM-41, SBA-15 and the like;

[0025] The alumina carrier has a specific surface area of ​​80-240 m 2 / g, preferably 100-200m 2 / g; pore volume is 0.5-1.5cm 3 / g, preferably 0.6-1.2cm 3 / g, the proportion of pore volume corresponding to pores with pore diameters greater than 100 nm to the total pore volume is ≮10%.

[0026] In the present invention, the preparation steps of the metal impregnation solution in step (2) are as follows:

[0027] (A) mixing an active metal compound, an organic acid, hydrogen peroxide and purified water to prepare an active metal aqueous solution;

[0028] (B) adding a composite complexing agent to the aqueous solution of step (A) to obtain an active metal impregnation solution.

[0029] The active metal compound of step (A) comprises at least one metal selected from Group VIII and one metal selected from Group VIB, wherein the metal of Group VIII is preferably nickel and / or cobalt, and most preferably nickel, and the metal of Group VIB is preferably molybdenum and / or tungsten, and most preferably molybdenum. The Group VIII metal nickel is one or more of basic nickel carbonate, nickel sulfate, nickel nitrate, nickel acetate, and nickel chloride, and is preferably nickel nitrate and nickel acetate. The Group VIB metal molybdenum raw material is one or more of molybdenum trioxide, ammonium heptamolybdate (ammonium molybdate tetrahydrate), ammonium tetramolybdate, ammonium orthomolybdate, ammonium octamolybdate, and ammonium dodecamolybdate, and is preferably molybdenum trioxide and ammonium heptamolybdate.

[0030] The organic acid in step (A) comprises at least one or more of tartaric acid, oxalic acid, malic acid, citric acid, succinic acid, and maleic acid, preferably oxalic acid, and the amount added is 1.0-12.0 g / 100 cm 3 .

[0031] The amount of hydrogen peroxide added in step (A) is 0.1-3.0 g / 100 cm 3 .

[0032] The specific preparation process of the active metal aqueous solution in step (A) is as follows:

[0033] a) mixing the Group VIB metal raw material and the organic acid in a container, adding deionized water, heating at 60-100° C. and stirring to completely dissolve them;

[0034] b) adding a Group VIII metal raw material to the solution obtained in step a), stirring and dissolving, and heating appropriately if necessary, to obtain an active metal mixture solution;

[0035] c) adding hydrogen peroxide to the solution obtained in step b) to obtain an active metal aqueous solution.

[0036] The composite complexing agent in step (B) is a combination of a polycarboxylic acid scale inhibitor and an organic phosphorus-containing compound. The polycarboxylic acid scale inhibitor includes at least one or more of polyepoxysuccinic acid, polyacrylic acid, hydrolyzed polymaleic anhydride, maleic acid-acrylic acid copolymer, polyaspartic acid, acrylic acid-hydroxypropyl acrylate copolymer (T-225), and acrylic acid-2-acrylamide-2-methylpropanesulfonic acid copolymer, and the addition amount is 0.5-15.0 g / 100 cm 3 The organic phosphorus-containing compound includes at least one or more of aminotrimethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, hydroxyethylenediphosphonic acid, and ethylenediaminetetramethylenephosphonic acid, and the addition amount is 0.5-10.0 g / 100 cm 3 .

[0037] The impregnation method of step (2) can be an equal volume impregnation method or a supersaturated impregnation method, etc.; the impregnation method can spray the solution onto the surface of the carrier, or immerse the carrier in the solution; the impregnation process can be performed by vacuuming the carrier or directly impregnating it; the impregnation process can be performed by heating the carrier or at room temperature; the impregnation process can be performed using auxiliary technologies such as ultrasound or microwaves.

[0038] In the step (2), the sample after immersion is cured under closed conditions at a temperature of 20-100°C, preferably 20-60°C, for 0.5-6 hours, preferably 1.0-4 hours; the drying conditions are 80-180°C, preferably 100-140°C, and the drying time is 1-6 hours, preferably 2-4 hours.

[0039] In the step (2), the calcination temperature is 400-700° C., preferably 420-600° C.; the calcination time is 0.5-6 hours, preferably 1-4 hours.

[0040] In the inferior residue oil hydrodemetallization catalyst, calculated as oxide, the VIB group metal accounts for 2-12% of the total weight of the catalyst, and the VIII group metal accounts for 0.4-3% of the total weight of the catalyst.

[0041] The low-quality residue oil hydrodemetallization catalyst has a specific surface area of ​​80-180m2 / g, pore volume is 0.5-1.1cm 3 / g, the proportion of pore volume corresponding to pores with pore diameters greater than 100 nm to the total pore volume is ≮10%.

[0042] A catalyst for hydrodemetallization of low-quality residual oil prepared by the above method.

[0043] Compared with the prior art, the low-quality residue oil hydrodemetallization catalyst and its preparation method of the present invention have the following advantages:

[0044] (1) Phenolic resin is used as a pore-enlarging agent, which is partially dissolved under the action of low-carbon alcohols. After extension and cross-linking, a macroporous diffusion channel with a diameter of more than 100 nm is formed in the alumina carrier. It has low cost, is both thermoplastic and thermosetting, is easy to shape, and has high carrier strength.

[0045] (2) Use organic acids to prepare the metal solution system. Organic acid radical ions have coordination sites that can form coordination bonds with metal ions. By coordinating with active metal ions, organic acid radical ions can form stable complexes with them. Organic acids are weakly acidic and can reduce the corrosion loss of the carrier. The addition of hydrogen peroxide can cause redox reactions under acidic conditions, promote the active metal to form relatively stable oxidation products, weaken the interaction between the active components and the alumina carrier, and can have a positive effect on the activity and stability of the final residue oil hydroprocessing catalyst. Volatile ammonia is not used in the preparation process of the metal impregnation solution, the solution system is green and environmentally friendly, and the production process is environmentally friendly.

[0046] (3) Use a composite complexing agent, which has strong complexing ability and good solution stability. Through efficient complexing, the length of the metal active phase crystal is shortened, the number of crystal layers is reduced, and a larger proportion of 1-2 layer crystal structures are generated, so as to achieve high dispersion loading of active metals and improve catalyst activity and stability. The use of organic phosphorus-containing compounds in the composite complexing agent introduces an appropriate amount of phosphorus into the acidic active metal solution system, which can effectively weaken the strong interaction between the active components and the carrier, optimize the metal active phase structure, and thus improve the dispersion of active metals in the residual oil hydroprocessing catalyst. At the same time, it avoids the problems of excessive phosphorus, excessive acidity, and aggregation of metal components caused by the use of phosphoric acid to prepare the acidic system of the active metal solution, prevents the increase in the number and length of the catalyst active phase, and avoids the decrease in stability during the catalyst hydrogenation reaction, and has stronger processing adaptability to inferior residual oil. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 : TEM transmission electron microscope image of catalyst B in Example 2.

[0048] Figure 2 : TEM transmission electron microscope image of catalyst D in Example 4.

[0049] Figure 3 : TEM transmission electron microscope image of catalyst G in comparative example 1.

[0050] Figure 4 : Mercury intrusion pore size distribution diagram of catalyst A in Example 1. DETAILED DESCRIPTION

[0051] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0052] Embodiment 1:

[0053] Weigh 500g of PN-2 macroporous pseudo-boehmite dry glue powder (dry basis content 71.5wt%) produced by Binzhou Poly Innovation Materials Co., Ltd., add 35.8g of phenolic resin powder with a particle size of 1000 mesh and 10.7g of hydroxypropyl methylcellulose with a viscosity of 150,000 mPa·s (referring to the viscosity of a 2% aqueous solution at 20°C), and mix well; dissolve 10g of ethanol in 607.8g of clean water, heat to 60°C, slowly add to the above materials, knead into a plastic body, and then extrude into a clover shape with a diameter of 1.6mm on a single screw extruder; dry at 140°C for 2.0 hours, then place in a high-temperature roasting furnace, and keep at a constant temperature of 900°C for 3 hours to obtain a carrier a. The physicochemical properties of the carrier a are shown in Table 1.

[0054] Weigh 2.0g of molybdenum trioxide and 1.0g of oxalic acid respectively, place them in a beaker, add 60g of deionized water, heat and stir at 95℃ to dissolve; weigh 2.08g of nickel nitrate, add, stir and dissolve; cool the solution to room temperature, add 0.5g of 20% hydrogen peroxide gradually under stirring; add 0.5g of polyacrylic acid and 0.5g of diethylene triamine penta methylene phosphonic acid, stir and dissolve, and then calibrate to 100cm 3 , and obtain the active metal impregnation solution. Weigh 50g of carrier a, and use the equal volume impregnation method to spray the impregnation solution onto carrier a. The impregnated sample is cured under a closed condition of 20℃ for 1 hour; dried under 110℃ for 2 hours; the dried sample is calcined at a constant temperature of 550℃ for 4 hours to obtain residual oil hydroprocessing catalyst A. After the catalyst is sulfided, the results of the transmission electron microscope (TEM) analysis of the active phase are shown in Table 2.

[0055] Embodiment 2:

[0056] Weigh 500g of PN-2 macroporous pseudo-boehmite dry glue powder (dry basis content 71.5wt%) produced by Binzhou Poly Innovation Materials Co., Ltd., add 71.5g of phenolic resin powder with a particle size of 120 mesh and 17.9g of hydroxypropyl methylcellulose with a viscosity of 50,000 mPa·s (referring to the viscosity of a 2% mass concentration aqueous solution at 20°C), and mix well; dissolve 17.9g of ethanol in 607.8g of clean water, heat to 80°C, slowly add to the above materials, knead into a plastic body, and then extrude into a clover shape with a diameter of 1.6mm on a single screw extruder; dry at 160°C for 1.0 hour, then place in a high-temperature roasting furnace, and keep at a constant temperature of 700°C for 4 hours to obtain a carrier b. The physicochemical properties of the carrier b are shown in Table 1.

[0057] Weigh 7.68g of molybdenum trioxide and 4.0g of oxalic acid, place in a beaker, add 60g of deionized water, heat and stir at 60℃ to dissolve; weigh 5.54g of nickel nitrate, add, stir and dissolve; cool the solution to room temperature, add 6.0g of 20% hydrogen peroxide gradually under stirring; add 4.0g of epoxysuccinic acid and 3.0g of aminotrimethylenephosphonic acid under stirring, stir and dissolve at room temperature, and standardize the solution to 100cm 3 50 g of carrier b was weighed, and the impregnation liquid was impregnated onto the alumina carrier b by spraying using an equal volume impregnation method. The impregnated sample was cured at 40°C for 4 hours under closed conditions; dried at 100°C for 4 hours; and the dried sample was calcined at 500°C for 2 hours to obtain a residual oil hydroprocessing catalyst B. After the catalyst was sulfided, the results of the active phase transmission electron microscopy (TEM) analysis are shown in Table 2.

[0058] Embodiment 3:

[0059] Weigh 500 g of PN-2 macroporous pseudo-boehmite dry glue powder (dry basis content 71.5 wt%) produced by Binzhou Poly Innovation Materials Co., Ltd., add 17.9 g of phenolic resin powder with a particle size of 2000 mesh and 3.6 g of hydroxypropyl methylcellulose with a viscosity of 200,000 mPa·s (referring to the viscosity of a 2% aqueous solution at 20° C.), and mix well; dissolve 1.8 g of ethanol in 607.8 g of clean water, heat to 40° C., slowly add to the above materials, knead into a plastic body, and then extrude into a clover shape with a diameter of 1.6 mm on a single screw extruder; dry at 120° C. for 3.0 hours, then place in a high-temperature roasting furnace, and keep it at a constant temperature of 1000° C. for 1 hour to obtain a carrier c. The physicochemical properties of the carrier c are shown in Table 1.

[0060] Weigh 11.53g of ammonium heptamolybdate and 6.0g of oxalic acid, place in a beaker, add 60g of deionized water, heat at 98°C and stir to dissolve; weigh 6.47g of nickel acetate, add, stir to dissolve; cool the solution to room temperature, add 7.5g of 20% hydrogen peroxide gradually under stirring; add 4.0g of hydrolyzed polymaleic anhydride and 10.0g of hydroxyethylidene diphosphonic acid under stirring, stir to dissolve at room temperature, and standardize the solution to 100cm 3 50 g of carrier c was weighed, and the impregnation liquid was impregnated onto the alumina carrier c by spraying using an equal volume impregnation method. The impregnated sample was cured at 45°C for 2 hours under closed conditions; dried at 120°C for 2 hours; and the dried sample was calcined at 600°C for 1 hour to obtain a residual oil hydroprocessing catalyst C. After the catalyst was sulfided, the results of the active phase transmission electron microscopy (TEM) analysis are shown in Table 2.

[0061] Embodiment 4:

[0062] Weigh 500 g of the aforementioned pseudo-boehmite dry rubber powder, add 53.6 g of 300-mesh phenolic resin powder, add 10.7 g of hydroxypropyl methylcellulose with a viscosity of 150,000 mPa·s, and mix well; dissolve 14.3 g of methanol in 600.0 g of clean water, heat to 50°C, slowly add to the aforementioned materials, knead into a plastic body, and then extrude into a clover shape with a diameter of 1.6 mm on a single-screw extruder; dry at 130°C for 3 hours, then place in a high-temperature roasting furnace, and keep the temperature at 800°C for 2 hours to obtain carrier d. The physicochemical properties of carrier d are shown in Table 1.

[0063] Weigh 11.81g of molybdenum trioxide and 8.0g of oxalic acid, place in a beaker, add 65g of deionized water, heat and stir at 100°C to dissolve; weigh 8.33g of nickel nitrate, add, stir and dissolve; cool the solution to room temperature, add 9.0g of 20% hydrogen peroxide gradually under stirring; add 6.0g of hydrolyzed polymaleic anhydride and 4.0g of ethylenediaminetetramethylenephosphonic acid under stirring, stir and dissolve at room temperature, and standardize the solution to 100cm 3 50 g of the carrier d was weighed, and the impregnation liquid was impregnated onto the alumina carrier d by spraying using an equal volume impregnation method. The impregnated sample was cured at 60°C for 3 hours under closed conditions; dried at 140°C for 2 hours; and the dried sample was calcined at 480°C for 2 hours to obtain a residual oil hydrotreating catalyst D. After the catalyst was sulfided, the results of the active phase transmission electron microscopy (TEM) analysis are shown in Table 2.

[0064] Embodiment 5:

[0065] Weigh 500 g of the aforementioned pseudo-boehmite dry rubber powder, add 25.0 g of phenolic resin powder with a particle size of 600 mesh, add 10.7 g of hydroxypropyl methylcellulose with a viscosity of 150,000 mPa·s, and mix well; dissolve 7.2 g of ethanol and 7.2 g of methanol in 603.0 g of clean water, heat to 50°C, slowly add to the aforementioned materials, knead into a plastic body, and then extrude into a clover shape with a diameter of 1.6 mm on a single-screw extruder; dry at 130°C for 3 hours, then place in a high-temperature roasting furnace, and keep the temperature at 950°C for 3 hours to obtain carrier e. The physicochemical properties of carrier e are shown in Table 1.

[0066] Weigh 14.31g of molybdenum trioxide and 11.0g of oxalic acid, place in a beaker, add 65g of deionized water, heat and stir at 85°C to dissolve; weigh 8.73g of nickel nitrate, add, stir and dissolve; cool the solution to room temperature, add 12.0g of 20% hydrogen peroxide gradually under stirring; add 15.0g of polyacrylic acid and 6.0g of ethylenediaminetetramethylenephosphonic acid under stirring, stir and dissolve at room temperature, and standardize the solution to 100cm 3 50 g of the above-mentioned carrier e was weighed, and the impregnation liquid was impregnated onto the alumina carrier e by spraying using an equal volume impregnation method. The impregnated sample was cured under a closed condition of 40°C for 4 hours; dried under a condition of 120°C for 3 hours; and the dried sample was calcined at a constant temperature of 460°C for 3 hours to obtain a residual oil hydrotreating catalyst E. After the catalyst was sulfided, the results of the transmission electron microscopy (TEM) analysis of the active phase are shown in Table 2.

[0067] Embodiment 6:

[0068] Weigh 500 g of the aforementioned pseudo-boehmite dry rubber powder, add 28.6 g of phenolic resin powder with a particle size of 200 mesh, add 10.7 g of hydroxypropyl methylcellulose with a viscosity of 150,000 mPa·s, and mix well; dissolve 10.7 g of ethanol in 600.0 g of clean water, heat to 55°C, slowly add to the aforementioned materials, knead into a plastic body, and then extrude into a clover shape with a diameter of 1.6 mm on a single-screw extruder; dry at 120°C for 3 hours, then place in a high-temperature roasting furnace, and keep the temperature at 850°C for 3 hours to obtain a carrier f. The physicochemical properties of the carrier f are shown in Table 1.

[0069] Weigh 18.0g of molybdenum trioxide and 12.0g of oxalic acid, place in a beaker, add 60g of deionized water, heat and stir at 90°C to dissolve; weigh 20.83g of nickel nitrate, add, stir and dissolve; cool the solution to room temperature, add 15.0g of 20% hydrogen peroxide gradually under stirring; add 8.0g of epoxysuccinic acid and 5.0g of hydroxyethylidene diphosphonic acid under stirring, stir and dissolve at room temperature, and standardize the solution to 100cm 350 g of the carrier f was weighed, and the impregnation liquid was impregnated onto the alumina carrier f by spraying using an equal volume impregnation method. The impregnated sample was cured at 55°C for 2 hours under closed conditions; dried at 110°C for 3 hours; and the dried sample was calcined at 420°C for 3 hours to obtain a residual oil hydroprocessing catalyst F. After the catalyst was sulfided, the results of the active phase transmission electron microscopy (TEM) analysis are shown in Table 2.

[0070] Comparative Examples 1-3 illustrate the prior art process and the residue hydroprocessing catalysts prepared by the prior art process.

[0071] Comparative Example 1:

[0072] Comparative Example 1 is to prepare the alumina carrier according to the method described in CN105983443B, and to prepare the metal impregnation solution according to the method provided in CN114425354B. The catalyst metal loading is the same as that in Example 2.

[0073] Weigh 500g of macroporous pseudo-boehmite dry rubber powder (dry basis content 71.5wt%) produced by Yantai Henghui Chemical Co., Ltd., add 10.7g of hydroxypropyl methylcellulose with a viscosity of 150,000 mPa·s (referring to the viscosity of 2% aqueous solution) and 17.9g of polyvinyl alcohol powder with a particle diameter of 90-150μm, and mix them evenly; dissolve 14.3 grams of boric acid in 390g of clean water, slowly add it to the above materials, knead it into a plastic body, and then extrude it into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder. Dry it at 120℃ for 2.0 hours, then place it in a roasting furnace and keep it at 800℃ for 3 hours to obtain carrier g, and its physical and chemical properties are shown in Table 1.

[0074] Weigh 7.68g of molybdenum trioxide and 2.61g of basic nickel carbonate, place them in a beaker, add water and stir, weigh 3.76g of phosphoric acid, dilute with water and slowly add to the beaker, react at room temperature for 15 minutes; heat to 95°C and heat for 35 minutes; weigh 3.0g of citric acid and add, continue to heat at constant temperature for 25 minutes, wait until all the raw materials are dissolved, turn off the heating and cool to room temperature; add 10.0g of triethanolamine and 3g of Tween-80 while stirring, stir and dissolve, and calibrate to 100cm 3 The impregnation liquid was impregnated on the carrier g by spraying, and the impregnated sample was dried and kept at 500°C for 2 hours to obtain catalyst G. After the catalyst was sulfurized, the results of the active phase transmission electron microscopy (TEM) analysis are shown in Table 2.

[0075] Comparative Example 2:

[0076] Comparative Example 2: An alumina carrier was prepared by referring to the method described in CN1103009A, and a metal impregnation solution was prepared by referring to the method disclosed in CN103007949B. The catalyst metal loading was the same as that in Example 2.

[0077] 34.1 g of aluminum hydroxide dry rubber powder (alkyl aluminum hydrolysis product containing 75% aluminum oxide) and 39.3 g of aluminum hydroxide powder obtained by the aluminum sulfate method were mixed, and then 4.7 g of high-wear-resistant carbon black, 3.5 g of surfactant SA-20, 2.1 g of aluminum nitrate and 66 ml of water were added and fully rolled and mixed. The mixture was extruded into a clover shape with a diameter of 1.8 mm on an extruder, dried at 120°C, and calcined at 600°C for 4 hours to obtain carrier h. Its physical and chemical properties are shown in Table 1.

[0078] Take 30% hydrogen peroxide and add it dropwise to 9.48g ammonium heptamolybdate, stirring to dissolve; add 5.54g nickel nitrate, stirring to dissolve, add 1.5g terephthalic acid, calibrate to 100cm 3 The solution was added dropwise onto carrier h, impregnated at room temperature for 6 hours, dried at 110°C for 2 hours, and calcined at 500°C for 4 hours to obtain catalyst H. After the catalyst was sulfurized, the results of transmission electron microscopy (TEM) analysis of the active phase are shown in Table 2.

[0079] Comparative Example 3:

[0080] Comparative Example 3: The alumina carrier was prepared by referring to the method described in patent CN1647857A, and the metal impregnation solution was prepared by referring to the method disclosed in patent CN1230491C. The catalyst metal loading was the same as that in Example 2.

[0081] Weigh 500 g of PN-2 macroporous pseudo-boehmite dry rubber powder (aluminum sulfate-sodium aluminate method, dry basis content 71.5 wt%) produced by Binzhou Poly Innovation Materials Co., Ltd., add 10.7 g of polyethylene glycol with a molecular weight of 2000, add water to slurry, and finally obtain 6 liters of slurry, then spray dry at an inlet temperature of 580°C and an outlet temperature of 180°C. The resulting composition is extruded and dried, and calcined at 800°C for 3 hours to obtain carrier i, whose physicochemical properties are shown in Table 1.

[0082] Take 75cm 3 Ammonia water with a concentration of 18% was placed in an ultrasonic transducer, and the transmission power was controlled to be 350W and the frequency to be 25kHz. 9.48g of ammonium heptamolybdate was added and dissolved, and then 5.54g of nickel nitrate was added. After the metal salt was completely dissolved, the ultrasonic transducer was turned off and the volume of the solution was adjusted to 100cm with ammonia water. 3 The solution was added dropwise onto carrier i, impregnated at room temperature for 4 hours, dried at 120°C for 2 hours, and calcined at 500°C for 3 hours to obtain catalyst I. After the catalyst was sulfurized, the results of transmission electron microscopy (TEM) analysis of the active phase are shown in Table 2.

[0083] Embodiment 7:

[0084] This example is an activity evaluation test of the catalysts obtained in Examples 1-6 and Comparative Examples 1-3, and is used to compare the hydrogenation reaction performance of catalysts prepared by different methods.

[0085] The above-mentioned catalysts B, G, H and I were subjected to performance tests on a fixed bed residue oil hydrogenation evaluation device using the same feedstock oil and process conditions. The feedstock oil properties and process conditions are listed in Table 3, and the evaluation results are listed in Table 4.

[0086] In summary, it can be seen from Examples 1-7 and Comparative Examples 1-3 that:

[0087] (1) From the carrier physical property data in Table 1, it can be seen that compared with the prior art, the carrier obtained in the present invention has the characteristics of large pore volume and pore diameter, high proportion of macropores above 100 nm and good strength, and can better adapt to the hydrodemetallization process of inferior residual oil;

[0088] (2) From the TEM characterization results in Table 2, it can be seen that the catalyst for hydrotreating residual oil obtained by the present invention has a small number of lamellae, mainly single-layer and double-layer MoS2, short lamellae length, good active phase dispersion, and obvious high dispersion, low stacking, and short lamellae characteristics, which are more suitable for the hydrotreating of heavy and inferior residual oil; while the catalyst obtained in the comparative example has a high proportion of lamellae structure with more than 3 layers, a large lamellae length, and poor dispersion of active components;

[0089] (3) As can be seen from the evaluation results in Table 4, compared with the comparative example catalyst, the catalyst prepared by the present invention has better desulfurization, carbon removal and demetallization activity, good activity stability, and stronger adaptability to inferior raw material processing, which is beneficial to extend the operation cycle of the device and improve economic benefits.

[0090] Table 1 Physical and chemical properties of carriers

[0091]

[0092]

[0093] Table 2 Catalyst TEM characterization results

[0094]

[0095] Table 3 Evaluation test raw oil and process conditions

[0096] Raw oil properties Middle East Residue <![CDATA[Density (20 °C) / g·cm -3 > 0.9884 Sulfur content, w% 4.478 Carbon residue value, w% 13.20 <![CDATA[Metal (Ni + V), μg·g -1 > 79.44 Process conditions Reaction temperature, °C 380 Hydrogen partial pressure, MPa 16.0 <![CDATA[Space velocity, h -1 > 1.0 Hydrogen / oil ratio, V / V 700

[0097] Table 4 Catalyst evaluation results

[0098]

Claims

1. A method for preparing a catalyst for hydrodemetallization of low-quality residual oil, characterized in that: The following steps are involved: (1) mixing hydrated alumina, phenolic resin and a binder, adding an aqueous solution containing a low-carbon alcohol, kneading, forming, drying and calcining to obtain an alumina carrier; (2) dissolving the metal compound by using an organic acid and hydrogen peroxide, adding a complex complexing agent, and preparing a metal impregnation solution; impregnating the carrier in step (1), curing, drying, and calcining to obtain a catalyst; The active metal compound comprises at least one metal selected from Group VIII and one metal selected from Group VIB, and the metal of Group VIB accounts for 2-12% of the total weight of the catalyst and the metal of Group VIII accounts for 0.4-3% of the total weight of the catalyst in terms of oxide; The specific surface area of ​​the inferior residue oil hydrodemetallization catalyst is 80-180m 2 / g, pore volume is 0.5-1.1cm 3 / g, the proportion of pore volume corresponding to pores with pore diameters greater than 100 nm to the total pore volume is ≮10%.

2. The preparation method according to claim 1, characterized in that: The steps of preparing the metal impregnation solution in step (2) include: (A) mixing an active metal compound, an organic acid, hydrogen peroxide and purified water to prepare an active metal aqueous solution; (B) adding a composite complexing agent to the aqueous solution of step (A) to obtain an active metal impregnation solution; The organic acid includes at least one or more of tartaric acid, oxalic acid, malic acid, citric acid, succinic acid, and maleic acid; The composite complexing agent is a combination of a polycarboxylic acid scale inhibitor and an organic phosphorus-containing compound; The polycarboxylic acid scale inhibitor includes at least one or more of polyepoxysuccinic acid, polyacrylic acid, hydrolyzed polymaleic anhydride, maleic acid-acrylic acid copolymer, polyaspartic acid, acrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-2-acrylamide-2-methylpropane sulfonic acid copolymer; The organic phosphorus-containing compound includes at least one or more of aminotrimethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, hydroxyethylenediphosphonic acid, and ethylenediaminetetramethylenephosphonic acid.

3. The preparation method according to claim 2, characterized in that: The specific preparation process of the active metal aqueous solution in step (A) is as follows: (a) Mixing a Group VIB metal raw material and an organic acid in a container, adding deionized water, heating at 60-100° C. and stirring to completely dissolve the mixture; (b) adding a Group VIII metal raw material to the solution obtained in step (a), stirring and dissolving, and heating appropriately if necessary, to obtain an active metal mixture solution; (c) adding hydrogen peroxide to the solution obtained in step (b) to obtain an active metal aqueous solution.

4. The preparation method according to claim 1, characterized in that: In the step (2): The impregnated samples are cured in a closed environment at a temperature of 20-100°C for 0.5-6 hours; The drying condition is 80-180°C and the drying time is 1-6 hours; The calcination temperature is 400-700° C., and the calcination time is 0.5-6 hours.

5. The preparation method according to claim 1, characterized in that: The hydrated aluminum oxide is selected from one or a mixture of gibbsite, boehmite, pseudo-boehmite and amorphous aluminum hydroxide.

6. The preparation method according to claim 1, characterized in that: The phenolic resin is a condensation product of phenol and formaldehyde, and can be thermosetting or thermoplastic or a mixture of the two, and its particle size is 80-3000 mesh; the addition amount is 2-25wt% based on aluminum oxide.

7. The preparation method according to claim 1, characterized in that: The binder is synthetic cellulose, selected from one or more of methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl methyl cellulose, and the addition amount is 1-5wt% based on aluminum oxide; The viscosity of a 2% mass concentration aqueous solution of the synthetic cellulose at 20° C. is not less than 50,000 mPa·s.

8. The preparation method according to claim 1, characterized in that: The low-carbon alcohol is selected from one or more of methanol, ethanol, ethylene glycol, propanol, isopropanol and glycerol, and the added amount is 0.5-5wt% based on alumina; The temperature of the aqueous solution containing low-carbon alcohol is 30-100°C.

9. The preparation method according to claim 1, characterized in that: The drying temperature of the alumina carrier is 100-180°C; the calcination temperature of the alumina carrier is 500-1200°C, and the calcination time is 1-4 hours; The shape of the alumina carrier includes any one of a bar, a sphere, a Raschig ring, a toothed ball, a honeycomb, and an impeller; The auxiliary agent includes one or more of silicon, phosphorus, boron, titanium, zirconium, chlorine and fluorine; The molecular sieve added to the alumina carrier includes one or more of X, Y, ZSM-5, β, phosphorus aluminum, titanium silicon, ZSM-41, and SBA-15; The specific surface area of ​​the alumina carrier is 80-240m 2 / g, pore volume 0.5-1.5cm 3 / g, the proportion of pore volume corresponding to pores with pore diameters greater than 100 nm to the total pore volume is ≮10%.

10. A low-quality residue oil hydrodemetallization catalyst prepared according to the method for preparing a low-quality residue oil hydrodemetallization catalyst according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Process for producing hydrofining catalyst

    CA2370726A1

  • Aluminum oxide carrier and preparation method thereof

    CN104549534A

  • Hydrorefining catalyst preparation method

    CN109692685A

  • Bulk phase hydrofining catalyst and preparation method thereof

    CN111822006A

  • Inferior residual oil hydrodemetallization catalyst and preparation method thereof

    CN115245830A